Advancing Cross-Organizational Collaboration in Aircraft Development - Baalbergen, E.H.; Vankan, W.J.; Boggero, L.; Bussemaker, J.H.; Lefèbvre, T.; Beijer, B.; Bruggeman, A.M.R.M.; Mandorino, M. (Netherlands Aerospace Centre NLR, 2022)
Efficient collaboration between engineers is a key enabler for successful development of any modern aircraft and its numerous systems and components. Because of their highly complex and integrated nature, effective collaboration demands well-organized, multi-disciplinary, multi-engineer, and cross-organizational development processes. Such processes depend on automated, data-driven, computer-assisted tools and methodologies. Effective collaboration may seem as simple as working together, adopting standards and tools, and freely sharing data, information, and knowledge. However, in the development of complex systems such as aircraft, collaboration is, alas, not that straightforward. For example, aircraft engineers across disciplines and organizations commonly face challenges such as security firewalls, data and tool heterogeneity, and intellectual property protection issues. In this technical paper we review the collaboration challenges. Next, we describe how collaboration supporting technologies developed and integrated in the EU-funded research project AGILE 4.0 provide engineering teams with solutions to face such challenges. The technologies comprise solutions for shared access to design information, for collaborative systems engineering, for creating and using collaborative cross-organization multi-disciplinary analysis and optimization workflows that facilitate integrated use of distributed tools and data thereby complying with applicable security constraints, and for managing the creation and use of surrogate models. We finally detail the application of and experiences with these collaboration supporting technologies.
This report is based on a presentation held at the 2022 AIAA Aviation Forum, Chicago, IL, USA & Online, 27 June – 1 July 2022.